IMPLEMENTATION OF BALANCED SCORECARD AT PT. MB - Randi Lukmanto; Dwi Bakti Iriantini; Indahwati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to determine the performance of PT. MB uses a balanced scorecard approach. Primary data were obtained from questionnaires using the nonprobability sampling purposive sampling method. Data obtained from customers and employees of PT. MB. Secondary data obtained from the financial statements of PT. MB period 2020 to 2022. The population is all customers and employees of PT. MB. The samples used were 94 samples for customers and 72 samples for employees. The data analysis method uses descriptive statistical test techniques. To determine the level of customer and employee satisfaction scores using factor analysis. The results of the balanced scorecard study on a financial perspective have an average performance from 2020 to 2022 for ROA has an average of 3.18%, ROE 3%, and NPM 2.30%. From a customer perspective, it is measured through a questionnaire with an average customer satisfaction level of 3,559. Customer acquisition costs have averaged $3.35. Consumer profitability has an average value of 3.10%. In the internal business process preceptive, the AETR ratio has an average of 11.55%. The time cycle of availability of goods has an actual time of 8.09. Sales order cancellation 0.8%. From a growth and learning perspective, the average employee productivity rate is 0.39%. Employee training has an average of 66.67%. And the level of employee satisfaction showed an average of 3,108.